PENERAPAN TINDAK PIDANA PENIPUAN DAN PENGGELAPAN DALAM PELAKSANAAN PERJANJIAN PENGELOLAAN LIMBAH INDUSTRI - Santoso, Budi; Maryano, Maryano; Ismed, Mohamad (SINERGI : Jurnal Riset Ilmiah, 2025)
This phenomenon frequently occurs in cooperative practices between industrial companies and waste management operators, where business actors fail to fulfill their contractual obligations, such as not processing waste in accordance with established procedures, concealing essential facts, or abusing trust for personal gain. Such actions may be classified as the criminal offense of fraud as stipulated in Article 378 of the Indonesian Criminal Code (KUHP) and embezzlement under Article 372 of the KUHP.The research problems in this study are: (1) How is the application of the criminal offenses of fraud and embezzlement in the implementation of industrial waste management agreements? and (2) How are legal protection measures provided to the aggrieved party in the execution of such agreements?The research method employed is normative juridical, using statutory, conceptual, and case approaches. The results of the study indicate that although an agreement constitutes a civil legal relationship, if there is malicious intent (mens rea) from the outset, such conduct may be brought into the realm of criminal law. Furthermore, law enforcement against perpetrators may be pursued through criminal proceedings by law enforcement authorities, while victims may seek remedies through both criminal and civil legal channels as forms of legal protection.This study contributes to strengthening legal certainty and legal protection for parties involved in non-B3 waste management agreements, as well as serving as a preventive measure against crimes detrimental to the environment and society. The core analysis of this study focuses on material losses, the object of the agreement (non-B3 waste), and the ownership of waste materials in accordance with the contractual terms.